Victimization of indigenous women workers in informal sectors: A study in Tangail District, Bangladesh - Mahmud, Md. Sohel; Faruk, Md. Omar; Hossain, T. M. Mosharraf (International Journal of Emerging Trends in Social Sciences, 2025)
This study explores the victimization of indigenous women workers across various employment sectors. Using a descriptive survey design, data were collected from a randomly selected sample of 60 indigenous women workers from two upazilas in Tangail District. A structured questionnaire, titled- “Victimization of Indigenous Women Workers in Informal Sectors: A Study in Tangail District, Bangladesh” was utilized alongside interviews to gather in-depth insights into their experiences. Data analysis was conducted using multiple cross-tabulations and chi-square statistics. The findings revealed a significant relationship between age and types of victimization (physical, psychological, sexual, and economic) as well as between offender type and the nature of victimization in the workplace. Furthermore, the study identified a statistically significant association between occupation and physical victimization (χ² = 12.539, df = 5, p < 0.05) and between monthly income and working hours (χ² = 10.945, df = 8, p < 0.05). Based on these findings, the study recommends several interventions to mitigate the victimization of indigenous women workers, including ensuring workplace safety, challenging patriarchal attitudes, reducing power imbalances, strengthening labor laws, implementing gender sensitivity training, and establishing comprehensive workplace policies. These measures can contribute to a safer, more equitable, and inclusive work environment for indigenous women.